Anchorage evaluation of dental implants irradiated with GaAIAs laser (830nm) - Bruno Campanha (2007)
The aim of the present study was to evaluate titanium implants fixed with free rotation in rabbit's tibia and irradiated with GaAlAs laser (4.3Joules/daily, 830nm wavelength, 12mW and 51 seconds) using a digital torquimeter. Thirty male rabbits were divided into two groups (Laser and Control) and subdivided according to their death day 15 (L1 and C1), 30 (L2 and C2) and 45 (L3 and C3) after surgery. A digital torquimeter evaluated the torque needed for removing the implants, breaking their union to the bone. The results were submitted to Student's "t" test and ANOVA test, in order to validate these findings. It was observed an increase on removal torque values of irradiated implants both with 15 and 30 days after surgery, in comparison to control groups. With 45 days, there was no statistically significant difference between the Laser and Control groups values. It was concluded that Laser group showed a higher value in the removal torque when compared to non-irradiated implants.